Evaluasi Sistem Saluran Drainase di Jalan Raya Candi II Kecamatan Klojen, Kota Malang - Kiki Frida Sulistyani; Suhudi Suhudi; Umbu Lete Daha (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
A drainage channel for a water structure that can properly drain water to the downstream section of a channel. A channel capable of accommodating Qrencana will be able to free the city from flooding. The issue of flooding is a concern for various parties, especially the local community, and the government also has an important role to play. The research location is on Jalan Raya Candi II, Klojen District, Malang City, East Java. The design flow calculation method uses the rational method with a 5-year and 10-year return period. The flood discharge for a 5-year return period is 3585 m3/second and for a 10-year return period is 3934 m3/second. At the research location, there are a total of 6 channel sections and after evaluation, 1 channel is still sufficient to accommodate the design flood discharge for a 5-year and 10-year return period. However, there are 5 channels that are insufficient to accommodate the design flood discharge for a 5-year and 10-year return period. For channels that are insufficient, they need to be redesigned with Q5years added to the protection height (W) and controlled with Q10years to obtain the appropriate capacity in an effort to prevent flooding at the research location. The redesign of channel 1 is b = 2.4 m and channel height = 2.1 m in the channel design. The channel dimensions are the same from channel 1 to channel 6, and a storage well is recommended to overcome surface water runoff.